PEMASARAN DAN PENGEMBANGAN OBJEK KAWASAN WISATA BALONGAN REMBANG MELALUI DESTINATION BRANDING - Rikah, Rikah; Damayanti, Damayanti; Susanti, Ari (Fokus ABDIMAS, 2023)
This community service program is carried out in the Balongan Kragan beach area in Rembang Regency. One of the problems or weaknesses faced by Partners is the low level of knowledge about marketing management and the limited application of marketing management in developing tourist attractions. So the team formulated a program to develop the Balongan beach tourist area through destination branding. Holding marketing management training, one of which is discussion and mentoring for partners, namely managers of the Balongan Beach tourist area. The material provided in tourism marketing and development training includes: 1) Marketing Management, 2) Destination Branding of Tourist Attractions, 3) Advertising communication strategies and 4) Creative Strategies in Tourist Attraction Development. It is hoped that this service activity can increase the economic value of the Balongan beach area. Keyword: marketing, development, tourism, and destination branding.